Soft tissue head and neck sarcoma: experience of a tertiary referral centre over a 15-year period. Issue 12 (29th December 2019) - Harrison, L; McCulloch, T; Beasley, N
Abstract: Background: Head and neck soft tissue sarcoma is uncommon. It is both histologically and clinically heterogeneous, ranging from an indolent, locally destructive tumour, to a locally aggressive neoplasm with metastatic potential. Methods: A retrospective review was conducted of all adult head and neck soft tissue sarcomas, including cases of malignant soft tissue sarcoma and all intermediate type tumours, diagnosed between 1997 and 2012. Results: Sixty-eight cases were identified in this series from the sarcoma multidisciplinary team. Seventeen different histological subtypes of sarcoma were identified. Neither age, gender nor tumour size were significant prognostic indicators for survival in this series. Conclusion: Prognosis is dependent on histological subtype, underscoring the importance of histological classification. Some histological subtypes occur only once or twice in a decade, even within a large regional referral centre. An accumulation of evidence from relatively small case series is key in the long-term development of treatment strategies.